Several Hermite-Hadamard Type Inequalities for Harmonically Convex Functions in the Second Sense with Applications (Communications in Mathematical Research, 2021)
In this paper, we first introduce the concept "harmonically convex functions" in the second sense and establish several Hermite-Hadamard type inequalitiesfor harmonically convex functions in the second sense. Finally, some applications tospecial mean are shown.